Penyelesaian Pembiayaan Bermasalah pada Akad Mudharabah di BMT Duta Jaya - Muhamad Nasrulloh; Muhamad Nadratuzzaman Hosen (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Mudharabah Financing Agreement is a contract with profitability that is quite beneficial for the parties. In practice, there are often problems and disputes in the financing contract. This study aims to analyze the procedure for solving problematic financing disputes in mudharabah contracts conducted by BMT Duta Jaya using descriptive-normative methods that describe research subjects and objects based on apparent facts and legal approaches used to study the legal norms of the law data that has been obtained. The results of this study indicate that the problem solvings procedure for financing disputes in Duta Jaya Lampung BMT uses non-litigation method. In the implementation of the contract, all mudarabah contract financing operations are in accordance with DSN fatwa number 07/DSN-MUI/IV/2000, only there are fines or compensation provisions which incur members to bear it without any reason